Lithium ion secondary battery

By introducing sodium ion additives into the electrolyte of the lithium-ion secondary battery and adjusting the peak area ratio of the Na element of the positive and negative electrode sheets, the problem of transition metal element dissolution in the positive electrode material under high temperature conditions is solved, and better cycling and kinetic performance is achieved.

CN119742414AActive Publication Date: 2025-04-01CALB GROUP CO LTD

Patent Information

Application Number
CN202411839730.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-01
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

During the circulation process of lithium-ion secondary batteries, especially under high temperature conditions, transition metal elements in the positive electrode material will dissolve, lose active lithium, increase interface impedance, reduce the stability of the electrolyte, and affect the circulation performance of the battery.

Method used

The sodium ion additive is introduced into the electrolyte of the battery, and the peak area ratio of the Na element at the surface layer of the positive electrode sheet and the negative electrode sheet at a depth of 30 nm is within the range of 0.1≤X/Y≤0.95 to optimize the dissolution of transition metal elements in the positive electrode material, reduce the loss of active lithium, and improve the dynamic performance of the battery.

Benefits of technology

By introducing sodium ion additives and controlling the peak area ratio of Na elements, the dissolution of transition metal elements in the positive electrode material is effectively suppressed, the protection effect of the negative electrode sheet is improved, and the circulation performance of the battery is improved, especially in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005187670140000141
    Figure BDA0005187670140000141
  • Figure BDA0005187670140000151
    Figure BDA0005187670140000151
  • Figure BDA0005187670140000152
    Figure BDA0005187670140000152
Patent Text Reader

Abstract

The invention discloses a lithium ion secondary battery, and belongs to the technical field of batteries. According to the technical scheme, a sodium ion additive is introduced into an electrolyte in the battery, and meanwhile, the ratio of the peak area of Na elements in an XPS test of active material layers of a positive pole piece and a negative pole piece under the surface layer depth of 30 nm is regulated and controlled to be within a specific range; the dissolution phenomenon of transition metal elements in the positive electrode material under a high-temperature condition can be effectively optimized, the loss of active lithium is reduced, the dynamic performance of the battery is improved, the protection effect on a negative electrode plate is improved, and finally the cycle performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a lithium-ion secondary battery. Background Art

[0002] Lithium-ion secondary batteries generally use compounds containing transition metal elements (such as lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, etc.) as positive electrode materials. However, during the cycle of lithium-ion secondary batteries, especially under high temperature conditions, the transition metal elements in the positive electrode material will dissolve into the electrolyte in the form of ions, losing a considerable amount of active lithium, and further migrate to the interface of the negative electrode, increasing the interface impedance; on the other hand, these ions will also reduce the stability of the electrolyte, causing it to undergo chemical reactions to produce by-products, ultimately affecting the battery's cycle performance. Summary of the invention

[0003] The purpose of the present application is to overcome the shortcomings of the prior art and provide a lithium-ion secondary battery, which can effectively optimize the dissolution of transition metal elements in the positive electrode material under high temperature conditions, reduce the loss of active lithium, improve the battery kinetics, enhance the protection effect on the negative electrode, and ultimately improve the battery cycle performance by introducing sodium ion additives into the electrolyte of the battery and regulating the Na element peak area ratio of the active material layers of the positive electrode plate and the negative electrode plate at a depth of 30nm on the surface in a specific range.

[0004] To achieve the above-mentioned object, in a first aspect of the present application, the present application provides a lithium-ion secondary battery, including a positive electrode sheet, a negative electrode sheet and an electrolyte;

[0005] The electrolyte contains a sodium ion additive;

[0006] The positive electrode plate includes a current collector and a positive electrode material layer, and the negative electrode plate includes a current collector and a negative electrode material layer;

[0007] The lithium ion secondary battery satisfies: 0.1≤X / Y≤0.95;

[0008] Wherein, X is the characteristic peak area of ​​the Na element when the positive electrode plate is subjected to XPS test and the XPS etching depth is 30 nm on the side of the positive electrode material layer away from the current collector; Y is the characteristic peak area of ​​the Na element when the negative electrode plate is subjected to XPS test and the XPS etching depth is 30 nm on the side of the negative electrode material layer away from the current collector.

[0009] The beneficial effects of this application are:

[0010] The present application provides a lithium-ion secondary battery, which can effectively optimize the dissolution of transition metal elements in the positive electrode material under high temperature conditions, reduce the loss of active lithium, improve the battery kinetics, enhance the protection effect on the negative electrode, and ultimately improve the battery cycle performance by introducing a sodium ion additive into the electrolyte of the battery and regulating the Na element peak intensity ratio of the active material layers of the positive electrode plate and the negative electrode plate at a depth of 30nm on the surface in a specific range in the XPS test. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 This is the XPS spectrum result of the characteristic peak area of ​​the Na element at an XPS etching depth of 30 nm on the side of the positive electrode material layer away from the current collector when the positive electrode sheet of the lithium-ion secondary battery described in Example 1 of the present application is tested during XPS testing.

[0012] Figure 2 This is the XPS spectrum result of the characteristic peak area of ​​the Na element at an XPS etching depth of 30 nm on the side of the negative electrode material layer away from the current collector when the negative electrode plate is tested during XPS testing of the lithium-ion secondary battery described in Example 1 of the present application. DETAILED DESCRIPTION

[0013] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0014] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0015] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0016] The present application is further described below with specific embodiments:

[0017] A lithium-ion secondary battery comprises a positive electrode sheet, a negative electrode sheet and an electrolyte;

[0018] The electrolyte contains a sodium ion additive;

[0019] The positive electrode plate includes a current collector and a positive electrode material layer, and the negative electrode plate includes a current collector and a negative electrode material layer;

[0020] The lithium ion secondary battery satisfies: 0.1≤X / Y≤0.95;

[0021] Wherein, X is the characteristic peak area of ​​the Na element when the positive electrode plate is subjected to XPS test and the XPS etching depth is 30 nm on the side of the positive electrode material layer away from the current collector; Y is the characteristic peak area of ​​the Na element when the negative electrode plate is subjected to XPS test and the XPS etching depth is 30 nm on the side of the negative electrode material layer away from the current collector.

[0022] In some specific embodiments, the coordinates of the characteristic peak area are 1070-1075 eV.

[0023] The positive electrode material in the lithium-ion secondary battery will undergo transition metal element dissolution during the battery cycle, especially in a high-temperature environment. This will not only consume active lithium, but also affect the interfacial impedance of the negative electrode and the stability of the electrolyte, ultimately weakening the battery's cycle performance. In the lithium-ion secondary battery described in the present application, a sodium ion additive is added to the electrolyte. The additive can form an inorganic SEI film on the negative electrode in advance during the battery cycle, and then further react at high temperature to form a highly stable organic / inorganic composite SEI film; on the other hand, during the battery charging process, the additive will also form a high-density CEI film on the positive electrode. The combined action of the two generated films inhibits the dissolution of transition metal elements in the positive electrode material and effectively protects the negative electrode; at the same time, the present application also regulates the XPS ((X-ray Photoelectron Spectroscopy) of the positive and negative electrode sheets under an etching of 30nm Spectroscopy) tests the characteristic peak area ratio of the sodium element, which can effectively regulate the thickness relationship of the respective SEI / CEI film layers generated by the sodium ion additive on the corresponding pole piece, so that the lithium ion secondary battery can have both pole piece stability and a lower DCR growth rate during the cycle in a high temperature environment to improve the kinetic performance, the negative pole piece passivation effect is good, the pole piece interface impedance is low, the degree of interface side reaction is low, the lithium ion transmission efficiency is high, and the cycle performance is excellent. In some embodiments, the lithium ion secondary battery satisfies: X / Y = 0.1, 0.2, 0.21, 0.23, 0.25, 0.3, 0.35, 0.38, 0.4, 0.5, 0.55, 0.6, 0.65, 0.7, 0.73, 0.75, 0.8, 0.9, 0.95, one or any two of the range values.

[0024] Regulating the ratio of the Na element XPS characteristic peak areas of the two electrodes at the same etching depth can directly affect the electrochemical performance of the lithium-ion secondary battery. If the ratio is too large, the kinetic performance of the lithium-ion secondary battery will deteriorate, and the SEI film will not provide sufficient passivation protection for the negative electrode, and the battery's cycle capacity will decay severely under high temperature conditions. If the ratio is too small, the interface stability in the positive electrode material will be insufficient, and the kinetic performance will also be low, and the battery will still not be able to achieve ideal electrochemical performance. Therefore, the ratio needs to be maintained within the above range.

[0025] In some embodiments, the lithium ion secondary battery satisfies: 0.21≤X / Y≤0.75. More preferably, the lithium ion secondary battery satisfies: X / Y=0.21, 0.23, 0.25, 0.3, 0.35, 0.38, 0.4, 0.5, 0.55, 0.6, 0.65, 0.7, 0.73, 0.75, or any two of the range values.

[0026] When the Na element XPS characteristic peak area ratio of the two pole pieces under specific conditions is within the above preferred range, the overall ion / electron transmission efficiency of the lithium-ion secondary battery is higher, and better cycle performance in a high temperature environment can be achieved.

[0027] In some embodiments, X=1000-19000.

[0028] More preferably, X is a range of one or two of 1000, 2400, 2500, 3000, 3500, 4000, 5000, 5500, 6000, 6500, 6800, 6850, 7000, 8000, 9000, 10000, 11000, 12000, 13000, 14000, 14500, 15000, 16000, 17000, and 19000.

[0029] More preferably, X=2000-18000.

[0030] In some embodiments, Y=11000-25000.

[0031] Further preferably, Y=one or any two of the range values ​​of 11000, 12500, 13000, 13500, 14000, 15000, 16000, 16500, 17000, 18000, 18050, 18500, 19000, 20000, 21000, 21500, 22000, 23000, 25000.

[0032] More preferably, Y=12000-24000.

[0033] When the characteristic peak area X of the Na element in the XPS test of the positive electrode sheet under specific conditions changes, the dissolution degree and dissolution rate of the transition metal elements of the active material in the positive electrode sheet will be different, and the impedance size and the degree of interface side reaction of the positive electrode sheet interface will also be different; on the other hand, the size of the characteristic peak area Y of the Na element in the XPS test of the negative electrode sheet under specific conditions is related to the interface stability of the negative electrode sheet. When the values ​​of the two are preferably within the above range, the comprehensive stability and interaction of the two pole sheets are higher, the effective transmission amount and transmission efficiency of lithium ions between the two pole sheets are better, and the cycle and kinetic performance at high temperature are better.

[0034] In the technical scheme of the present application, the test method of X and Y is: disassemble the lithium-ion secondary battery in the empty state, soak the obtained positive electrode sheet or negative electrode sheet in dimethyl carbonate at room temperature for 60 minutes, take it out, dry it, and then fix it in the test mold with conductive tape, and use the NEXSAGA model XPS etching analyzer for testing. After the test is completed, the test result value of X or Y can be obtained by area integration from the test sample XPS spectrum according to the test data of the corresponding coordinates. Among them, the test conditions of XPS are: using a 120W monochromatic Al Kα X-ray source; energy resolution is less than or equal to 0.48eV; test beam spot is 400μm, and the instrument automatically supplements the test energy range according to the element to be tested; etching treatment conditions are: using Ar ions for etching, by adjusting the etching rate or etching time, etc., the etching surface is one side of the positive electrode material layer or one side of the negative electrode material layer, and the etching depth is controlled to be 30nm. After the test is completed, the test result value of X or Y can be read from the test sample XPS spectrum.

[0035] In some embodiments, the positive electrode material layer comprises a positive electrode material, and the lithium ion secondary battery satisfies: 0.05×10 -3 ≤W / X≤7.5×10 -3 ; Where W = (D v 90-D v 10) / D v 50,D v 90 is the particle size corresponding to when the cumulative distribution percentage of the positive electrode material reaches 90%; D v 50 represents the particle size corresponding to when the cumulative distribution percentage of the positive electrode material reaches 50%; D v 10 represents the particle size corresponding to when the cumulative distribution percentage of the positive electrode material reaches 10%.

[0036] More preferably, W / X=0.05×10 -3 , 0.1×10 -3 , 0.3×10-3 , 0.6×10 -3 , 0.8×10 -3 , 0.9×10 -3 , 1×10 -3 , 1.2×10 -3 , 1.5×10 -3 , 1.8×10 -3 , 2×10 -3 , 2.5×10 -3 , 2.8×10 -3 , 3×10 -3 , 3.5×10 -3 , 4×10 -3 4.2×10 -3 4.36×10 -3 , 5×10 -3 , 6×10 -3 ,7×10 -3 , 7.5×10 -3 The range value of one or both of them.

[0037] Further preferably, the lithium-ion secondary battery satisfies: 0.1×10 -3 ≤W / X≤7×10 -3

[0038] W in this application is the positive electrode material D v 90.D v 50 and D v The particle size distribution span coefficient obtained by the combination of 10 can effectively measure the breadth of the particle size distribution of the positive electrode material, and is related to the wettability of the positive electrode material in the electrolyte, the dissolution efficiency of the transition metal elements, the quality of the CEI film formed by the electrolyte on the surface of the positive electrode plate, and the lithium ion transmission efficiency. When sodium ion additives are introduced into lithium-ion secondary batteries and the ratio of X and Y is controlled, by adjusting the breadth of the particle size distribution of the positive electrode material and the characteristic peak area of ​​the Na element XPS test under specific conditions of the positive electrode plate within the above-mentioned ratio range, the probability of additional side reactions on the surface of the positive electrode material after the electrolyte infiltrates the positive electrode material can be further reduced, the dissolution of the transition metal elements can be inhibited, and better electrochemical performance can be achieved.

[0039] In some embodiments, W=0.6-16.

[0040] Further preferably, W is a range of one or any two of 0.6, 0.8, 1, 1.2, 1.25, 1.5, 1.8, 2, 2.05, 2.2, 3, 3.01, 3.5, 5, 5.5, 8, 10, 12, 15, 16.

[0041] More preferably, W=1-15.

[0042] Further preferably, the D v 90 = 2.5 ~ 25 μm, D v 50 = 0.5 ~ 5 μm, D v 10=0.2~1μm.

[0043] Further preferably, the D v 90=2.5 ​​μm, 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm, or any two of the range values; the D v 50=0.5 μm, 0.6 μm, 0.8 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 2 μm, 5 μm, or any two of the range values; the D v 10=a range value of one or any two of 0.2 μm, 0.3 μm, 0.4 μm, 0.45 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, and 1 μm.

[0044] In the technical solution of this application, the D of the positive electrode material v 90.D v 50 and D v 10 Confirmed by the following test method: disassemble the lithium-ion secondary battery, then soak the positive electrode plate in dimethyl carbonate (DMC) for 60 minutes, take it out, dry it, scrape the positive electrode material layer on the positive electrode plate, and apply the obtained powder on the conductive glue for scanning electron microscopy observation at a magnification of 30,000 times. Then use the particle size measurement software Nano Measurer to grab 200 individual positive electrode material particles for particle size measurement, and finally confirm them according to the particle size distribution test results. Specifically, the size of the positive electrode material particles is measured on the SEM image using the MEARSURE NANO software, and the diagonal line method is used to collect the size of the positive electrode material particles. After the sample size reaches more than 200, the particle size distribution is statistically analyzed to calculate the particle size related parameters of the positive electrode material.

[0045] In some embodiments, the sodium ion additive includes at least one of sodium difluorooxalatoborate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethylsulfonyl)imide, and sodium difluorophosphate.

[0046] In the electrolyte of the lithium-ion secondary battery described in the present application, the sodium ion additive can be selected from but not limited to the above types. These sodium ion additives will be embedded in the surface of the negative electrode material during the high temperature environment cycle of the lithium-ion battery, and will first react to form an inorganic SEI film layer. At the same time, some intermediate compounds will further inflame to form an organic oligomer SEI film layer under the high temperature environment. Through the combination of two types of composite film layers, the negative electrode material layer on the negative electrode plate can be effectively quickly passivated on the negative electrode surface and protected; on the other hand, the sodium ion additive will also form a CEI film layer on the positive electrode surface, reducing the dissolution of transition metal ions, thereby reducing the loss of active lithium ions during the cycle. When the Na element XPS characteristic peak area ratio under specific conditions of the positive and negative electrode plates is further controlled within the specified range of the present application, the lithium-ion secondary battery can take into account both high stability and high cycle activity under high temperature environments, and achieve higher cycle retention and lower DCR growth rate.

[0047] In some embodiments, the mass percentage of the sodium ion additive in the electrolyte is 0.05-1.2%.

[0048] Further preferably, the mass percentage of the sodium ion additive in the electrolyte is 0.5-0.8%

[0049] By adjusting the content of sodium ion additives in the electrolyte, it is possible to avoid the situation where the sodium ion additive preferentially forms a film on the negative electrode sheet when the content is too small, thereby reducing the protective effect on the positive electrode sheet, increasing the dissolution concentration of transition metal ions on the positive electrode sheet, or reducing the kinetic performance of the positive and negative electrode sheets due to excessive addition.

[0050] In some embodiments, the electrolyte further includes a solvent and a lithium salt.

[0051] In some embodiments, the solvent includes at least one of a carbonate solvent, a carboxylate solvent, an ether solvent, a sulfone solvent, a nitrile solvent, and a phosphate solvent.

[0052] Exemplarily, the carbonate solvent includes but is not limited to at least one of propylene carbonate (PC), ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC); the carboxylate solvent includes but is not limited to at least one of ethyl acetate, methyl formate, and 1,4-butyrolactone; the ether solvent includes at least one of dimethyltetrahydrofuran, tetrahydrofuran, and 1,2-dimethoxyethane; the sulfone solvent includes at least one of methyl sulfone and dimethyl sulfoxide; the nitrile solvent includes at least one of propionitrile, butyronitrile, 1-(2-cyanoethyl)pyrrole, and 1,3,6-hexanetrinitrile; the phosphate solvent includes at least one of trimethyl triphosphate and triethyl phosphate.

[0053] In some embodiments, the lithium salt includes at least one of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium perchlorate, lithium tetrafluoroborate, lithium bisoxalatoborate, lithium difluorooxalatoborate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(trifluoromethanesulfonyl imide), lithium difluorobis(oxalatophosphate), lithium tetrafluorooxalatophosphate, and the like.

[0054] In some embodiments, the electrolyte further includes a second additive, and the second additive includes but is not limited to vinylene carbonate.

[0055] In some embodiments, the positive electrode material includes at least one of lithium iron manganese phosphate, lithium iron phosphate, doped lithium iron manganese phosphate, and doped lithium iron phosphate.

[0056] Further preferably, the doping element in the doped lithium manganese iron phosphate and the doped lithium iron phosphate includes at least one of V, W, Ti and Mg.

[0057] For example, the doped lithium manganese iron phosphate is LiMn x Fe y M z n PO4, wherein x is greater than 0 and less than 1; y is greater than 0 and less than 1; z is greater than or equal to 0 and less than 1; M refers to the doping element, and n refers to the valence of the doping element; the doped lithium manganese iron phosphate satisfies: 2(x+y)+n*z=2.

[0058] Further preferably, the positive electrode material also includes a carbon material.

[0059] Carbon materials, especially graphite and graphene with high conductivity and high adsorption efficiency, can take into account both improving the overall conductivity of the positive electrode material and inhibiting the dissolution of transition metal elements. Those skilled in the art can add a certain content and configuration of carbon materials to the positive electrode material to compound the lithium deintercalation active material according to actual conditions, as long as it does not affect the effect of the sodium ion additive in the electrolyte described in the technical solution of the present application and the regulation of the characteristic peak area ratio of the Na element in the electrode.

[0060] In some embodiments, the positive electrode material layer in the positive electrode plate includes a positive electrode material, a binder, and a conductive agent, and the mass percentage of the positive electrode material in the positive electrode material layer is 70 to 98%.

[0061] In some embodiments, the negative electrode material includes at least one of natural graphite, artificial graphite, mesophase carbon microbeads, hard carbon, soft carbon, elemental silicon, silicon oxide, silicon-carbon composite materials, and lithium titanate.

[0062] In some embodiments, the negative electrode material layer in the negative electrode plate includes a negative electrode material, a binder and a conductive agent, and the mass percentage of the negative electrode material in the positive electrode material layer is 70 to 99%.

[0063] The present invention is further described below with specific examples, which are not to be construed as limiting the scope of the present invention:

[0064] Example 1

[0065] A lithium ion secondary battery, the preparation method comprising the following steps:

[0066] (1) Preparation of positive electrode sheet: Grind and screen the positive electrode material LiMn 0.6 Fe 0.4 PO4, conductive agent carbon black and binder polyvinylidene fluoride were dispersed in N-methylpyrrolidone in a mass ratio of 96:1.5:2.5, and the slurry was prepared by vacuum stirring, and then coated on the current collector aluminum foil. The coating surface density was set to 400g / m 2 After drying, cold pressing and slitting, the 3 The compaction density is rolled to obtain the positive electrode sheet;

[0067] (2) Preparation of negative electrode sheet: artificial graphite of negative electrode material, carbon black of conductive agent, sodium carboxymethyl cellulose of thickener, and styrene-butadiene rubber of binder were dispersed in water at a mass ratio of 96.5:1:1:1.5, and the slurry was prepared by vacuum stirring, and then coated on the current collector copper foil, and the coating surface density was set to 180 g / m 2 After drying, cold pressing and slitting, the 3 The negative electrode sheet is obtained by rolling the negative electrode sheet with a compaction density of 100 μm.

[0068] (3) Preparation of electrolyte: EC and EMC were compounded in a mass ratio of 3:7 as a solvent, and then 13.5wt% of lithium hexafluorophosphate, as well as sodium ion additives, 1wt% FEC, 2wt% MMDS, 1wt% TMSP, and 2wt% VC film-forming additives were added based on the total mass of the electrolyte to obtain the electrolyte; the content of the sodium ion additive in the electrolyte is shown in Table 1;

[0069] (4) The positive electrode sheet, the commercially available PP separator, and the negative electrode sheet are stacked and wound in order to form a battery cell, and the battery cell is placed in an outer packaging shell, and after drying, an electrolyte is injected, and after vacuum packaging, standing, forming, and constant capacity, the lithium-ion secondary battery is obtained.

[0070] Among them, the steps of formation are:

[0071] (i) The lithium-ion secondary battery was charged at a constant current of 0.05C for 2 h, and then the rate was reduced to 0.33C and the constant current charging was continued for 2 h.

[0072] The parameters of the lithium ion secondary battery are shown in Tables 1 and 2, wherein A (wt%) represents the mass percentage of the sodium ion additive in the electrolyte, and D v 90 (μm) is the particle size corresponding to when the cumulative distribution percentage of the positive electrode material reaches 90%; D v 50 (μm) indicates the particle size corresponding to when the cumulative distribution percentage of the positive electrode material reaches 50%; D v 10 (μm) is the particle size corresponding to the cumulative distribution percentage of the positive electrode material reaching 10%. X and Y are confirmed by the above test method. Specifically, the XPS etching-test spectrum of the positive electrode sheet tested corresponding to X is as follows: Figure 1 As shown, the XPS etching-test spectrum of the negative electrode sheet corresponding to Y is as follows Figure 2 shown.

[0073] Embodiments 2 to 4

[0074] A lithium ion secondary battery, which differs from Example 1 in that the parameters are different, wherein X and Y are regulated by the mass percentage of the sodium ion additive in the electrolyte, and W is regulated by the grinding time of the positive electrode material and the screen used for particle screening.

[0075] Example 5

[0076] A lithium ion secondary battery, which differs from Example 1 in that the parameters are different, wherein X and Y are regulated by the formation step, and W is regulated by the grinding time of the positive electrode material and the screen used for particle screening;

[0077] The formation steps are:

[0078] (ii) The lithium ion secondary battery was cycled for 3 times at a working voltage of 2 to 2.5 V at a rate of 0.02 C, then charged at a constant current rate of 0.05 C for 2 h, and then the rate was reduced to 0.33 C and the constant current charging was continued for 2 h.

[0079] Example 6

[0080] A lithium ion secondary battery, which differs from Example 1 in that the parameters are different, wherein X and Y are regulated by the mass percentage of the sodium ion additive in the electrolyte, and W is regulated by the grinding time of the positive electrode material and the screen used for particle screening.

[0081] Example 7

[0082] A lithium ion secondary battery, which differs from Example 1 in that the parameters are different, wherein X and Y are regulated by the mass percentage of the sodium ion additive in the electrolyte and the formation step, and W is regulated by the grinding time of the positive electrode material and the screen used for particle screening;

[0083] The formation steps are:

[0084] (iii) The lithium-ion secondary battery was charged at a constant current of 0.05 C for 2 h, then the rate was reduced to 0.33 C and the constant current charging was continued for 2 h, and finally the rate was reduced to 0.1 C and the constant current charging was continued for 1 h.

[0085] Embodiments 8 to 10

[0086] A lithium ion secondary battery, which differs from Example 1 in that the parameters are different, wherein X and Y are regulated by the mass percentage of the sodium ion additive in the electrolyte, and W is regulated by the grinding time of the positive electrode material and the screen used for particle screening.

[0087] Embodiment 11

[0088] A lithium ion secondary battery, which differs from Example 1 in that the parameters are different, wherein X and Y are regulated by the mass percentage of the sodium ion additive in the electrolyte and the formation step, and W is regulated by the grinding time of the positive electrode material and the screen used for particle screening; the formation step is:

[0089] (iii) The lithium-ion secondary battery was charged at a constant current of 0.05 C for 2 h, then the rate was reduced to 0.33 C and the constant current charging was continued for 2 h, and finally the rate was reduced to 0.1 C and the constant current charging was continued for 1 h.

[0090] Example 12

[0091] A lithium ion secondary battery, which differs from Example 1 in that the parameters are different, wherein X and Y are regulated by the mass percentage of the sodium ion additive in the electrolyte, and W is regulated by the grinding time of the positive electrode material and the screen used for particle screening.

[0092] Embodiment 13

[0093] A lithium ion secondary battery, which differs from Example 1 in that the parameters are different, wherein X and Y are regulated by the mass percentage of the sodium ion additive in the electrolyte and the formation step, and W is regulated by the grinding time of the positive electrode material and the screen used for particle screening; the formation step is:

[0094] (iv) The lithium-ion secondary battery was charged at a constant current of 0.02C for 2 h, then the rate was reduced to 0.33C and the constant current charging was continued for 2 h, and finally the rate was reduced to 0.1C and the constant current charging was continued for 1 h.

[0095] Embodiments 14 to 18

[0096] A lithium ion secondary battery, which differs from Example 1 in that the parameters are different, wherein X and Y are regulated by the mass percentage of the sodium ion additive in the electrolyte, and W is regulated by the grinding time of the positive electrode material and the screen used for particle screening.

[0097] Embodiment 19

[0098] A lithium ion secondary battery, which differs from Example 1 in that the parameters are different, wherein X and Y are regulated by the mass percentage of the sodium ion additive in the electrolyte and the formation step, and W is regulated by the grinding time of the positive electrode material and the screen used for particle screening; the formation step is:

[0099] (v) The lithium-ion secondary battery was charged at a constant current of 0.08C for 2 h, then the rate was reduced to 0.33C and the constant current charging was continued for 2 h, and finally the rate was reduced to 0.1C and the constant current charging was continued for 1 h.

[0100] Embodiments 20 to 24

[0101] A lithium ion secondary battery, which is different from Example 1 in that the parameters are different, wherein X and Y are regulated by the mass percentage of the sodium ion additive in the electrolyte, and W is regulated by the grinding time of the positive electrode material and the screen used for particle screening.

[0102] Embodiment 25

[0103] A lithium ion secondary battery, which is different from Example 1 in that the parameters are different; wherein X and Y are regulated by the mass percentage of the sodium ion additive in the electrolyte and the formation step, and W is regulated by the grinding time of the positive electrode material and the screen used for particle screening;

[0104] The formation steps are:

[0105] (ii) The lithium ion secondary battery was cycled for 3 times at a working voltage of 2 to 2.5 V at a rate of 0.02 C, then charged at a constant current rate of 0.05 C for 2 h, and then the rate was reduced to 0.33 C and the constant current charging was continued for 2 h.

[0106] Embodiments 26 to 27

[0107] A lithium ion secondary battery, which differs from Example 1 in that the parameters are different, wherein X and Y are regulated by the mass percentage of the sodium ion additive in the electrolyte, and W is regulated by the grinding time of the positive electrode material and the screen used for particle screening.

[0108] Embodiment 28

[0109] A lithium ion secondary battery, which differs from Example 1 in that the parameters are different, wherein X and Y are regulated by the mass percentage of the sodium ion additive in the electrolyte and the formation step, and W is regulated by the grinding time of the positive electrode material and the screen used for particle screening;

[0110] The formation steps are:

[0111] (v) The lithium-ion secondary battery was charged at a constant current of 0.08C for 2 h, then the rate was reduced to 0.33C and the constant current charging was continued for 2 h, and finally the rate was reduced to 0.1C and the constant current charging was continued for 1 h.

[0112] Embodiment 29

[0113] A lithium-ion secondary battery, which is different from Example 1 in that when preparing the positive electrode plate, the positive electrode is made of LiFePO4 after grinding and particle screening.

[0114] Comparative Example 1

[0115] A lithium ion secondary battery, which differs from Example 1 in that the parameters are different, wherein X and Y are regulated by the mass percentage of the sodium ion additive in the electrolyte, and W is regulated by the grinding time of the positive electrode material and the screen used for particle screening.

[0116] Comparative Example 2

[0117] A lithium ion secondary battery, which differs from Example 1 in that the parameters are different, wherein X and Y are regulated by the mass percentage of the sodium ion additive in the electrolyte and the formation step, and W is regulated by the grinding time of the positive electrode material and the screen used for particle screening;

[0118] The formation steps are:

[0119] (vi) The lithium ion secondary battery was charged at a rate of 1C to a voltage of 2.5V, then charged at a rate of 0.33C to a voltage of 4V, and finally cycled for three times at a rate of 0.05C at an operating voltage of 4 to 4.3V.

[0120] Comparative Example 3

[0121] A lithium ion secondary battery, which differs from Example 1 in that the sodium ion additive is replaced by LiODFB of equal mass.

[0122] Comparative Example 4

[0123] A lithium ion secondary battery, which differs from Example 1 in that the parameters are different, wherein X and Y are regulated by the mass percentage of the sodium ion additive in the electrolyte and the formation step, and W is regulated by the grinding time of the positive electrode material and the screen used for particle screening;

[0124] The formation steps are:

[0125] (ii) The lithium ion secondary battery was cycled for 3 times at a working voltage of 2 to 2.5 V at a rate of 0.02 C, then charged at a constant current rate of 0.05 C for 2 h, and then the rate was reduced to 0.33 C and the constant current charging was continued for 2 h.

[0126] Comparative Example 5

[0127] A lithium ion secondary battery is different from the embodiment 1 in that the parameters are different, wherein X and Y are regulated by the mass percentage of the sodium ion additive in the electrolyte.

[0128] Comparative Example 6

[0129] A lithium ion secondary battery, which differs from Example 1 in that the parameters are different, wherein X and Y are regulated by the mass percentage of the sodium ion additive in the electrolyte and the formation step, and W is regulated by the grinding time of the positive electrode material and the screen used for particle screening;

[0130] The formation steps are:

[0131] (ii) The lithium ion secondary battery was cycled for 3 times at a working voltage of 2 to 2.5 V at a rate of 0.02 C, then charged at a constant current rate of 0.05 C for 2 h, and then the rate was reduced to 0.33 C and the constant current charging was continued for 2 h.

[0132] Comparative Example 7

[0133] A lithium ion secondary battery is different from the embodiment 1 in that the parameters are different, wherein X and Y are regulated by the mass percentage of the sodium ion additive in the electrolyte.

[0134] Table 1

[0135]

[0136]

[0137] Table 2

[0138]

[0139]

[0140] Effect example

[0141] The sodium ion secondary batteries obtained in each embodiment and comparative example were tested as follows:

[0142] (1) Cycle capacity retention test:

[0143] (I) At 45° C., the lithium ion secondary batteries obtained in the embodiments and comparative examples were cycled at a constant capacity for 3 times at a rate of 0.33C, and the third discharge capacity was taken as the initial capacity C1;

[0144] (II) Charge at a constant current rate of 1C to the upper limit voltage U 上限 , and then charged at a constant voltage to a rate ≤ 0.05C; wherein when the lithium ion secondary battery of Examples 1 to 28 and Comparative Examples 1 to 7 is charged at a constant current, U 上限 =4.3V, Example 29 corresponds to constant current charging of lithium ion secondary battery, U 上限 =3.65V;

[0145] (III) Let stand for 5 min;

[0146] (IV) Discharging at a rate of 1C to a voltage of 2.5V;

[0147] (V) let stand for 5 min;

[0148] (VI) Repeating steps (II) to (V) for 200 cycles of charge and discharge, and recording the battery capacity C2 after the cycle;

[0149] (VII) Calculate the cycle capacity retention rate % = 100% × C2 / C1. (2) DCR growth rate test:

[0150] (I) The lithium ion secondary batteries obtained in the embodiments and comparative examples were charged to a constant capacity at a rate of 0.33C, i.e., charged at a constant current and constant voltage of 0.33C to an upper limit voltage U 上限 , the current is less than or equal to 0.05C; then discharge at 0.33C to the lower limit voltage of 2.5V, repeat the above replenishment 3 times, take the third discharge capacity as the battery discharge capacity, discharge at 0.33C rate to adjust the charge to 50% SOC, let it stand for 2h, discharge at 1C for 18s, record the starting discharge voltage as V0, the voltage after 18s discharge is V1, the discharge current I1, calculate the initial battery internal resistance DCR1 = |V0-V1| / I1;

[0151] (II) The lithium-ion secondary battery is fully discharged at a constant current rate of 0.33C at 45°C to a lower limit voltage of 2.5V, and then the upper limit voltage U is increased from 2.5V to 1.5V at the same temperature. 上限 After 200 cycles of charge and discharge at 1C rate, the battery is charged at 0.33C constant current and constant voltage to the upper limit voltage U 上限, the current is less than or equal to 0.05C; then discharge at 0.33C to the lower limit voltage of 2.5V, repeat the above replenishment 3 times, take the third discharge capacity as the battery discharge capacity, discharge at 0.33C rate to adjust the charge to 50% SOC, let it stand for 2h, discharge at 1C for 18s, record the starting discharge voltage as V'0, the voltage after 18s discharge is V'1, the discharge current I'1, calculate the battery internal resistance after the cycle DCR2 = |V'0-V'1| / I'1;

[0152] (III) Calculate the DCR growth rate of the battery % = 100% × (DCR2-DCR1) / DCR1;

[0153] Examples 1 to 28 and Comparative Examples 1 to 7 correspond to the U of the lithium ion secondary battery. 上限 =4.3V, Example 29 corresponds to the U of the lithium ion secondary battery 上限 =3.65V;

[0154] The test results are shown in Table 3.

[0155] Table 3

[0156]

[0157]

[0158] From Table 3 we can see that:

[0159] (1) The lithium ion secondary battery described in the present application introduces a sodium ion additive into the electrolyte and simultaneously regulates the characteristic peak area ratio of the sodium element in the XPS test of the positive and negative electrode sheets under an etching of 30 nm, so that the lithium ion secondary battery can have both electrode stability and kinetic performance during the cycle process in a high temperature environment, the negative electrode sheet has a good passivation effect, the electrode sheet interface impedance is low, the degree of interface side reaction is low, the lithium ion transmission efficiency is high, and the capacity retention rate can reach more than 80% after 200 cycles at a 1C rate in a high temperature environment, and the DCR growth rate is not higher than 16.5%. In contrast, the lithium ion secondary battery obtained in Comparative Example 3, in which the sodium ion additive is not introduced but the conventional lithium ion additive is used to replace and configure the electrolyte, not only causes the loss of active lithium due to the serious dissolution of transition metal elements in the positive electrode material in the positive electrode sheet under a high temperature environment, but also the lithium ion secondary battery cannot quickly form a passivated thick SEI film on the surface of the negative electrode sheet during the cycle, and cannot form a thin and dense CEI film on the surface of the positive electrode sheet, and ultimately cannot achieve good high temperature cycle performance. The lithium ion secondary batteries described in Comparative Examples 1-2 and Comparative Examples 4-5 have sodium ion additives added to the electrolyte, but the ratio of X to Y is not well regulated. It can be seen that they still cannot achieve high cycle capacity retention and low DCR growth rate in a high temperature environment.

[0160] (2) According to Examples 1 to 11 and Examples 20 to 24, it can be seen that by adjusting the mass percentage of the sodium ion additive in the electrolyte and the formation steps, the values ​​of X and Y can be changed, and thus the range of the ratio of X / Y is also changed. When the ratio of X / Y is further preferably in the range of 0.21 to 0.75, the sodium ion additive can achieve a better effect during the cycle of the lithium ion secondary battery, the SEI film layer on the surface of the negative electrode plate has a higher degree of protection for the negative electrode material, making it more difficult for the transition metal elements to corrode the negative electrode material, the impedance of the positive electrode plate is low, and the kinetic performance between the plates is excellent. After 200 cycles at a rate of 1C under a high temperature environment, the capacity retention rate can reach more than 93% and the DCR growth rate is not higher than 11.5%.

[0161] (3) According to Examples 12 to 19 and Comparative Examples 6 to 7, it can be seen that the regulation of the positive and negative electrode plates X / Y described in the present application is not limited to a lithium-ion secondary battery under a sodium ion additive system. This limitation is applicable to different sodium ion additive systems. If X / Y is not in the range of 0.1 to 0.95, the lithium-ion secondary battery cannot achieve good cycle stability and conductivity at high temperatures. If X / Y is further preferably in the range of 0.21 to 0.75, the performance of the lithium-ion secondary battery is better.

[0162] (4) According to Examples 1 and 20 to 28, it can be seen that the particle size width W of the positive electrode material is related to the wettability of the positive electrode material in the electrolyte, the efficiency of transition metal dissolution, etc. When W / X is preferably 1×10 -3 ~7×10 -3 When the temperature is within the range of 200 °C, the positive electrode material impregnated with sodium ion additives can reduce the dissolution frequency of transition metal elements at high temperatures and reduce the probability of additional side reactions in the electrolyte while maintaining a high ion transfer efficiency, thereby improving the electrochemical performance of lithium-ion secondary batteries.

Claims

1. A lithium ion secondary battery, characterized in that: Including positive electrode sheet, negative electrode sheet and electrolyte; The electrolyte contains a sodium ion additive; The positive electrode plate includes a current collector and a positive electrode material layer, and the negative electrode plate includes a current collector and a negative electrode material layer; The lithium ion secondary battery satisfies: 0.1≤X / Y≤0.95; Wherein, X is the characteristic peak area of ​​the Na element when the positive electrode plate is subjected to XPS test and the XPS etching depth is 30 nm on the side of the positive electrode material layer away from the current collector; Y is the characteristic peak area of ​​the Na element when the negative electrode plate is subjected to XPS test and the XPS etching depth is 30 nm on the side of the negative electrode material layer away from the current collector.

2. The lithium ion secondary battery according to claim 1, characterized in that: The lithium ion secondary battery satisfies: 0.21≤X / Y≤0.

75.

3. The lithium ion secondary battery according to claim 1 or 2, characterized in that: The X=1000-19000, and / or the Y=11000-25000.

4. The lithium ion secondary battery according to claim 1, characterized in that: The positive electrode material layer contains a positive electrode material, and the lithium ion secondary battery satisfies: 0.05×10 -3 ≤W / X≤7.5×10 -3 ; Where W = (D v 90-D v 10) / D v 50,D v 90 is the particle size corresponding to when the cumulative distribution percentage of the positive electrode material reaches 90%; D v 50 represents the particle size corresponding to when the cumulative distribution percentage of the positive electrode material reaches 50%; D v 10 represents the particle size corresponding to when the cumulative distribution percentage of the positive electrode material reaches 10%.

5. The lithium ion secondary battery according to claim 4, characterized in that: The W=0.6~16.

6. The lithium ion secondary battery according to claim 1, characterized in that: The sodium ion additive includes at least one of sodium difluorooxalatoborate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethylsulfonyl)imide, and sodium difluorophosphate.

7. The lithium ion secondary battery according to claim 6, characterized in that: The mass percentage of the sodium ion additive in the electrolyte is 0.05-1.2%.

8. The lithium-ion secondary battery according to claim 1, wherein: The electrolyte also includes a solvent and a lithium salt; The solvent includes at least one of a carbonate solvent, a carboxylate solvent, an ether solvent, a sulfone solvent, a nitrile solvent, and a phosphate solvent, and / or the lithium salt includes at least one of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium perchlorate, lithium tetrafluoroborate, lithium bisoxalatoborate, lithium difluorooxalatoborate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(trifluoromethanesulfonyl imide), lithium difluorobis(oxalatophosphate), and lithium tetrafluorooxalatophosphate.

9. The lithium ion secondary battery according to claim 1, characterized in that: The positive electrode material includes at least one of lithium iron manganese phosphate, lithium iron phosphate, doped lithium iron manganese phosphate, and doped lithium iron phosphate, and / or the negative electrode material includes at least one of natural graphite, artificial graphite, mesophase carbon microbeads, hard carbon, soft carbon, elemental silicon, silicon oxide, silicon-carbon composite material, and lithium titanate.

10. An electrical device, characterized in that: The invention comprises the lithium ion secondary battery according to any one of claims 1 to 9, wherein the lithium ion secondary battery is used as a power supply for the electrical device.

Citation Information

Patent Citations

  • Oxide material containing Mg, Cu and Mn and preparation method and application of oxide material

    CN111525120A

  • Electrolyte for forming sulfate-based SEI (solid electrolyte interface) membrane as well as preparation and application of electrolyte

    CN115000508A

  • Quantitative detection method for lithium / sodium loss in negative electrode SEI layer of aged lithium / sodium ion battery

    CN117388304A

  • Secondary battery and device

    CN118539005A

  • Positive pole piece, secondary battery and electric device

    CN118969964A

Cited By

  • Battery cell, battery device and electric device

    CN120565800A